Dampak Kesiapan Perubahan Mempengaruhi Kualitas Sumber Daya Manusia dan Perilaku Inovatif terhadap Kinerja - Inra Kelana Bayu (IPM2KPE, 2024)
This research aims to investigate the influence of HR and Innovative Behavior on employee performance through Readiness for Change. The research method used is a quantitative descriptive method. The research results show that HR Quality and Innovative Behavior have a positive and significant influence on employee performance, both directly and through Readiness for Change. The conclusion is that it emphasizes the importance of having quality human resources and innovative behavior in improving employee performance, as well as the importance of readiness to change as a mediator in the relationship between these variables. Keywords: Readiness for Change, Quality of Human Resources, Performance, Innovative Behavior